Ocorrência de fungos dermatófitos e não dermatófitos em caixas de areia recreativas localizadas em creches públicas na cidade de Cuiabá - MT - Pereira, Ronaldo Sousa (2018)
Dermatophyte fungi are part of an important group with the ability to degrade keratin and cause superficial skin infections. The objective of this work was to isolate dermatophyte fungi and non-dermatophytic filamentous fungi in recreational sandboxes (rainy and dry period) in day care centers located in the city of Cuiabá-MT. The material analyzed consisted of 200 soil samples, collected from the superficial layer of sandboxes between 2-5 cm deep in 10 public nurseries chosen by lot. Hairs from 1 to 2 cm hairs were autoclaved and dispersed in 50 grams of the sample in sterile plates, incubated at 28 ° C, moistened where necessary with 50 mg / L chloramphenicol solution. After 6 weeks the baits were inoculated on Sabouraud agar plus (50 mg / L) chloramphenicol and (500 mg / L) cycloheximide. The fungi were identified according to macroscopic and micromorphological characteristics. From the sand samples collected, 1318 colonies were recovered, 56 fungal species belonging to 22 genera. The most isolated genera were Paecilomyces spp (30.42%), Penicillium spp (19.12%), Fusarium spp (11.46%) and Aspergillus spp (11.15%). Dermatophytes were isolated in 5 (50%) day care centers, making up a total of 29 colonies subsequently identified. Trichopthyton spp. (86.2%) was the most frequently recovered genus, followed by Microsporum sp. (13.8%). The isolation of dermatophytes in the recreational areas of day-care centers can pose a risk to the health of its users, especially to children and to the employees. The results obtained in this study suggest the need to monitor active leisure sandboxes for potentially pathogenic species.